Prevalence and influence of cys407 Grm2 mutation in Hannover-derived Wistar rats: mGlu2 receptor loss links to alcohol intake, risk taking and emotional behaviour - Wood, Christian M.; Nicolas, Celine S.; Choi, Sun-Lim; Roman, Erika; Nylander, Ingrid; Fernandez-Teruel, Alberto; Kiianmaa, Kalervo; Bienkowski, Przemyslaw; de Jong, Trynke R.; Colombo, Giancarlo; Chastagnier, Denis; Wafford, Keith A.; et al. (Neuropharmacology, 2017)
Modulation of metabotropic glutamate 2 (mGlu2) receptor function has huge potential for treating psychiatric and neurological diseases. Development of drugs acting on mGlu2 receptors depends on the development and use of translatable animal models of disease. We report here a stop codon mutation at cysteine 407 in Grm2 (cys407*) that is common in some Wistar rats. Therefore, researchers in this field need to be aware of strains with this mutation. Our genotypic survey found widespread prevalence of the mutation in commercial Wistar strains, particularly those known as Han Wistar. Such Han Wistar rats are ideal for research into the separate roles of mGlu2 and mGlu3 receptors in CNS function. Previous investigations, unknowingly using such mGlu2 receptor-lacking rats, provide insights into the role of mGlu2 receptors in behaviour. The Grm2 mutant rats, which dominate some selectively bred lines, display characteristics of altered emotionality, impulsivity and risk-related behaviours and increased voluntary alcohol intake compared with their mGlu2 receptor-competent counterparts. In addition, the data further emphasize the potential therapeutic role of mGlu2 receptors in psychiatric and neurological disease, and indicate novel methods of studying the role of mGlu2 and mGlu3 receptors. This article is part of the Special Issue entitled ‘Metabotropic Glutamate Receptors, 5 years on’. •Discovery of cys407* mutation in Grm2 of Wistar rats.•High prevalence in Han Wistar sub-strains.•Grm2 mutation linked with alcohol-preferring rats.•Grm2 mutation linked with changes in risk taking and emotional behaviour.